Rancang Bangun Pencatat Suhu Tanpa Kartu Memori Menggunakan Platform Micropython di Laboratorium Ilmu Pengetahuan Alam - Mochammad Darwis (UIN Sunan Kalijaga Yogyakarta, 2022)
This research is a continuation of the use of the micropython platform on the 32-bit ESP32 microcontroller. A temperature recorder that is compact, small in size and can store data for a certain period of time is needed in the science laboratory of SMP Negeri 1 Surabaya. Micropython can simplify hardware by eliminating memory hardware such as memory ICs or SD cards. The temperature data is stored in a file structure created in the micropython platform. The data is stored in the form of a text file so that it can be downloaded to a computer for graphing and analysis. The temperature sensor used is the DS18b20 type with a one-wire system. The one-wire system allows several sensors to be installed in parallel using only one data cable connected to the microcontroller. Temperature data collection was carried out for 26 minutes for every 3 seconds. The internal memory capacity that is used to store temperature data is 4 kilo bytes and the total memory space is 2 Mega bytes. The recorded data can be used for graphing and analysis.